Self-affirmation and an incongruent drinking norm: alcohol abuse prevention messages targeting young people. Issue 3 (3rd May 2016) - Voisin, Dimitri; Girandola, Fabien; David, Mathieu; Aim, Marie-Anastasie
Abstract: Many health campaigns are designed to reduce dangerous binge drinking by challenging the drinking perceived norm. Both information about health risks and statements that only a few people binge drink (descriptive norm) threaten self-integrity for individuals targeted. So, to combat this self-threat and preserve their positive self-integrity, drinkers discredit the message as a coping strategy. An alternative to the coping strategy is a procedure of self-affirmation to protect self-integrity. Across three experiments, we found that self-affirmation does indeed reduce (Experiment 1) or delete (Experiments 2 and 3) discrediting, but only provided that there is no normative information in the health message. Individuals continued to use the discrediting strategy despite the fact that the participants were self-affirmed when they are told that few people binge drink among their age group. The theoretical implications for self-affirmation are discussed.